Effect of Mixing Technology on Homogeneity and Quality of Sodium Naproxen Tablets: Technological and Analytical Evaluation Using HPLC Method - Mateusz Przywara; Regina Lech-Przywara; Patrycja Rupar; Wojciech Zapała (Molecules)
The uniform distribution of APIs is essential in tablet formulations, particularly in direct compression, where powder blending is the only means of ensuring dose homogeneity. This study evaluated the influence of three mixing techniques—V-type mixer, planetary ball mill, and vibratory ball mill—on the physical properties and content uniformity of naproxen sodium tablets. Blends consisting of naproxen sodium, cellulose, PVP, calcium carbonate, and magnesium stearate were prepared under varied mixing intensities and characterized in terms of flowability, compressibility, and particle size distribution. The resulting tablets were analyzed for weight, thickness, hardness, friability, and API content using a simplified bypass HPLC method. The V-type mixer yielded tablets with the most consistent weight and thickness, despite the poorest blend flow properties. Vibratory milling produced the hardest tablets and best API content uniformity, although high-energy processing introduced variability at longer mixing times. The analytical method proved fast and robust, allowing for reliable API quantification without full chromatographic separation. These findings underscore the need to balance mechanical blending energy with formulation properties and support the use of streamlined analytical strategies in pharmaceutical development.